2021
DOI: 10.1093/mnras/stab1958
|View full text |Cite
|
Sign up to set email alerts
|

The physical origins and dominant emission mechanisms of Lyman alpha haloes: results from the TNG50 simulation in comparison to MUSE observations

Abstract: Extended Lyman-alpha emission is now commonly detected around high redshift galaxies through stacking and even on individual basis. Despite recent observational advances, the physical origin of these Lyman-alpha halos (LAHs), as well as their relationships to galaxies, quasars, circumgalactic gas, and other environmental factors remains unclear. We present results from our new Lyman-alpha full radiative transfer code voroILTIS which runs directly on the unstructured Voronoi tessellation of cosmological hydrody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 117 publications
4
50
0
Order By: Relevance
“…Another way uses hydrodynamical simulations that resolve the gas around galaxies, which can be postprocessed with a Monte Carlo radiative transfer calculation to predict the shape of Lyα emission around galaxies (e.g., Lake et al 2015;Kimock et al 2021;Mitchell et al 2021). Most of these models simulate small numbers of galaxies, while Zheng et al (2011), Gronke &Bird (2017), andByrohl et al (2021) calculate Lyα radiative transfer in cosmological hydrodynamical simulations and offer predictions for large samples of galaxies. While being a promising tool, hydrodynamical simulations of galaxy formation in cosmological volumes with subkiloparsec resolutions (e.g., Nelson et al 2020) possibly suffer from convergence issues both in the physical gas state (e.g., van de Voort et al 2019) and in Lyα radiative transfer (e.g., Camps et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way uses hydrodynamical simulations that resolve the gas around galaxies, which can be postprocessed with a Monte Carlo radiative transfer calculation to predict the shape of Lyα emission around galaxies (e.g., Lake et al 2015;Kimock et al 2021;Mitchell et al 2021). Most of these models simulate small numbers of galaxies, while Zheng et al (2011), Gronke &Bird (2017), andByrohl et al (2021) calculate Lyα radiative transfer in cosmological hydrodynamical simulations and offer predictions for large samples of galaxies. While being a promising tool, hydrodynamical simulations of galaxy formation in cosmological volumes with subkiloparsec resolutions (e.g., Nelson et al 2020) possibly suffer from convergence issues both in the physical gas state (e.g., van de Voort et al 2019) and in Lyα radiative transfer (e.g., Camps et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of predictions with measurements draw different conclusions. While Steidel et al (2011), Gronke &Bird (2017), andByrohl et al (2021) find that most of the extended Lyα emission can be explained by scattering of Lyα photons from the central galaxy or nearby galaxies, Lake et al (2015) stressed the importance of cooling radiation in producing Lyα halos when they compared their simulation with observations from Momose et al (2014). Mitchell et al (2021) report that satellite galaxies are the predominant source of Lyα photons at 10-40 kpc, while cooling radiation also plays a relevant role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex interplay between gas inflows and outflows powered by supernova explosions or accreting black holes is known as the cosmic baryon cycle, and is a key ingredient to understanding galaxy formation and evolution (see Tumlinson et al 2017;Péroux & Howk 2020, for reviews). Both observations (Stocke et al 2013;Zhu et al 2014;Lan & Mo 2018;Zahedy et al 2019;Tchernyshyov et al 2021) and simulations (Oppenheimer et al 2018;Peeples et al 2019;Fielding et al 2020;Nelson et al 2020;Byrohl et al 2021) have revealed that the CGM is multi-phase and hosts gas with a wide range of temperatures and densities.…”
Section: Introductionmentioning
confidence: 99%
“…While multiple cosmological simulations have by now succeeded in reproducing the estimated masses of supermassive black holes at 𝑧 > 6, no attempt has been made to predict their associated extended Ly𝛼 emission with such simulations. Studies have begun to employ cosmological simulations to pin down the origin of extended Ly𝛼 emission, but these have mostly concentrated on massive haloes at 𝑧 ≈ 2 (Rosdahl & Blaizot 2012;Cantalupo et al 2014;Gronke & Bird 2017) or lower mass haloes (Smith et al 2019;Mitchell et al 2021;Byrohl et al 2021), in all cases without an on-the-fly treatment of quasar radiation.…”
Section: Introductionmentioning
confidence: 99%